SEMIOTICS IN ROBINSON CRUSOE AND HAYY IBN YAQZAN: A COMPARATIVE STUDY - Sistiadinita Sistiadinita; Hendro Kuncoro (UIN Alauddin Makassar, 2021)
ABSTRACTOne of the pioneering novels in English literature, Robinson Crusoe, tells of the story of a man who was thirsty for an adventure, finally made his destiny in an uninhabited island. Written by Daniel Defoe, this novel was said to have similarities with one of the stories in Islamic culture, Hayy Ibn Yaqzan, written by Ibn Tufayl. Hayy was narrated living in an unknown jungle, had nature as his best friends seeking to find the true meaning of life. The purpose of this research is to explore the meanings of the two novels written by authors with different cultural backgrounds and to analyze the meanings based on five reading codes proposed by Roland Barthes in Semiotic analysis; hermeneutic code, proairetic code, semic code, symbolic code and cultural / referential code. Roland Barthes developed this application of structural narrative analysis by splitting the text into lexias and grouping them into the codes. At the end, it was found out that authorial background, cultural representation and religious views of each author are the aspects which made the work unique from one to another. Meanwhile, the similarities are found in some aspects; spirituality, survival and progress, . Both authors present their own authenticity that it is difficult to justify whether Defoe took his reference from Hayy Ibn Yaqzan to create Robinson Crusoe.